2013
DOI: 10.1177/1078155213507010
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of bevacizumab in US elderly patients with colorectal cancer receiving chemotherapy

Abstract: Objective Bevacizumab, the first FDA-approved anti-angiogenesis agent, has been used for metastatic colorectal cancer since 2004. This study evaluated the utilization of bevacizumab among elderly metastatic colorectal cancer patients in the United States. Methods Using Surveillance and Epidemiology and End Results (SEER)-Medicare data, this retrospective cohort study consisted of individuals aged 65 years or older with a colorectal cancer diagnosis between 2005 and 2009, who received chemotherapy any time th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…9 Notably, the registry found that modern chemotherapeutic agents (ie, oxaliplatin, irinotecan, and bevacizumab) are increasingly being adopted for the elderly, perhaps suggesting a shift in practice patterns 9 ; although our study and other published analyses suggest that elderly patients were still significantly less likely to receive these agents than were younger patients. 4,19,29 Perhaps as a consequence, a significantly greater incidence of grade 1þ neutropenia was observed at baseline in younger patients than in elderly patients, 18,30 even in the relatively small number of patients evaluated for neutropenia in this study. Overall, we found that 90 Y-RE was equally well tolerated in eligible elderly (!…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…9 Notably, the registry found that modern chemotherapeutic agents (ie, oxaliplatin, irinotecan, and bevacizumab) are increasingly being adopted for the elderly, perhaps suggesting a shift in practice patterns 9 ; although our study and other published analyses suggest that elderly patients were still significantly less likely to receive these agents than were younger patients. 4,19,29 Perhaps as a consequence, a significantly greater incidence of grade 1þ neutropenia was observed at baseline in younger patients than in elderly patients, 18,30 even in the relatively small number of patients evaluated for neutropenia in this study. Overall, we found that 90 Y-RE was equally well tolerated in eligible elderly (!…”
Section: Discussionmentioning
confidence: 71%
“…[9][10][11][12][13] With an underrepresentation of elderly patients in clinical trials, 14 only a few population-based studies have evaluated the true impact of treatment on the elderly. 9,15 To date, there is little guidance on the best treatment strategy for elderly patients with CRC taking into consideration both age-related 16,17 and treatment-related factors [18][19][20] to improve outcomes. Only 1 report to date has specifically studied age in patients receiving radioembolization (RE) for hepatic metastases from CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of older adults treated with any anticancer medication did not increase during the 2009 to 2013 period, yet scientific evidence regarding the treatment of older adult cancer patients accrued during the period. It is unlikely that all these patients would not have benefited from conventional chemotherapy and/or targeted therapy, suggesting that physicians are still reluctant to prescribe anticancer medications for older adults . Factors associated with treatment with any anticancer medication compared with BSC were older age, health status, and physical function.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that all these patients would not have benefited from conventional chemotherapy and/or targeted therapy, suggesting that physicians are still reluctant to prescribe anticancer medications for older adults. 17 Factors associated with treatment with any anticancer medication compared with BSC were older age, health status, and physical function. Renal failure and malnutrition are undoubtedly predictive factors of poor efficacy or safety; this is less the case for other factors such as polymedication.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of therapy regimens and their efficacy have also been analyzed using the linked SEER-Medicare database. [33][34][35][36][37][38][39][40][41][42] Haynes et al found that although neoadjuvant chemoradiation followed by tumor resection and postoperative chemotherapy is the standard of care for patients with clinical stage II or III adenocarcinoma of the rectum, significant variation exists in the receipt of postoperative chemotherapy after resection in the elderly population with more than one in three patients failing to receive adjuvant therapy. 43 The abovementioned studies are just a selection of the numerous publications produced using the SEER and SEER-Medicare databases for the study of colorectal cancer.…”
Section: Seer-medicarementioning
confidence: 99%